Physicochemical characterization of nanobidentate ferrocene‐based Schiff base ligand and its coordination complexes: Antimicrobial, anticancer, density functional theory, and molecular operating environment studies. Issue 8 (17th June 2019) - Mahmoud, Walaa H.; Mahmoud, Nessma F.; Mohamed, Gehad G.
Abstract : A novel bidentate Schiff base ligand (HL, Nanobidentate Ferrocene based Schiff base ligand L (has one replaceable proton H)) was prepared via the condensation of 2‐amino phenol with 2‐acetyl ferrocene. The ligand was characterized using elemental analysis, mass spectrometry, infrared (IR) spectroscopy, 1 proton nuclear magnetic resonance (H‐NMR) spectroscopy, scanning electron microscopy ( SEM ), and thermal analysis. The corresponding 1:1 metal complexes with some transition‐metal ions were additionally characterized by their elemental analysis, molar conductance, SEM, and thermogravimetric ana1ysis (TGA). The complexes had the general formula [M(L)(Cl)(H2 O)3 ] x Cl· n H2 O (M = Cr(III), Mn(II), Fe(III), Co(II), Ni(II), Cu(II), Zn(II), and Cd(II)), ( x = 0 for Mn(II), Co(II), Ni(II), Cu(II), Zn(II), and Cd(II), x = 1 for Cr(III) and Fe(III)), ( n = 1 for Cr(III), n = 3 for Mn(II) and Co(II), n = 4 for Fe(III), Ni(II), Cu(II), Zn(II), and Cd(II)). Density functional theory calculations on the HL ligand were also carried out in order to clarify molecular structures by the B31YP exchange‐correlation function. The results were subjected to molecular orbital diagram, highest occupied mo1ecu1ar orbital–lowest occupied molecular orbital, and molecular electrostatic potential calculations. The parent Schiff base and its eight metal complexes were assayed against four bacterial species (two Gram‐negative and two‐Gram positive) and four different antifungal species. The HL ligand was docked using molecular operating environment 2008 with crystal structures of oxidoreductase (1CX2), protein phosphatase of the fungus Candida albicans (5JPE), Gram(−) bacteria Escherichia coli (3T88), Gram(+) bacteria Staphylococcus aureus (3Q8U), and an androgen‐independent receptor of prostate cancer (1GS4). In order to assess cytotoxic nature of the prepared HL ligand and its complexes, the compounds were screened against the Michigan cancer foundation (MCF)‐7 breast cancer cell line, and the IC50 values of compounds were calculated. Abstract : Schiff base ligand, HL and its eight new transition metal complexes were prepared and characterized using different tools. Molecular docking studies of the free Schiff base ligand and Cu(II) complex with receptors of different proteins reveal Cu(II) complex show highest binding ability and the minimum biding energy. The results of anticancer assay of ligand and the complexes suggested the Mn(II) complex exhibited the lowest IC50 was more effective against breast cancer cell line.